2015
DOI: 10.1007/s12070-015-0876-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nasal Allergy Over Spirometric Parameters: A Prospective Study

Abstract: Nasal allergy is characterized by an IgE mediated inflammatory response of nasal mucosa to allergens and it has a close association with Asthma. Nasal allergy has been demonstrated to be a strong risk factor for the onset of asthma in adults. Spirometric parameters like Forced expiratory volume at timed interval of 1 s (FEV1) and forced expiratory flow (FEF 25-75 % ) are impaired in patients with nasal allergy or allergic rhinitis. The FEF 25-75 % has been evidenced to be a reliable marker of early bronchial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Poorey et al. reported in their study that 45% had AEC between 501-800/mm 3 [ 14 ]. Eosinophils play an important role in allergic airway diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poorey et al. reported in their study that 45% had AEC between 501-800/mm 3 [ 14 ]. Eosinophils play an important role in allergic airway diseases.…”
Section: Discussionmentioning
confidence: 99%
“…in their study observed that all three parameters (FVC, FEV 1, and FEF 25–75% ) were impaired in 6% of subjects and two parameters (FEV 1 and FEF 25–75% ) were impaired in 9% of subjects and only parameter FEF 25–75% was found impaired in 64% of subjects. They concluded that FEF 25–75% is a marker of small airway impairment in asthmatics with normal FVC values [ 14 ]. Ciprandi et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with allergic rhinitis (AR) frequently have co-existing asthma (estimated at 10-40%) (17), while another 45% of AR individuals without asthma have bronchial hyperresponsiveness (18), an intermediate step toward asthma development. Selected studies have observed that individuals with AR can have an abnormal pulmonary function test (PFT) (19)(20)(21)(22)(23)(24) and fractional excretion of nitric oxide (FeNO) (25)(26)(27)(28)(29) even in the absence of asthma, suggesting that pollen is an important trigger for lower airway inflammation. In addition, FeNO has been shown to increase in sensitized individuals at times of higher pollen counts (27) and has been associated with the number of positive reactions on the SPT (25).…”
Section: Study Rationale For the Six Health Outcomes Pulmonary Outcomesmentioning
confidence: 99%